Visual Characteristics Study of Coffee Shop Signboards In Manggar Belitung Timur - Betha Almanfaluthi (Jurnal Titik Imaji, 2021)
The number of coffee shops at an adjacent location in Manggar made the city known as the City of 1001 Coffee Shops. 1001 Coffee Shop monument in Manggar, East Belitung confirmed that the tradition of drinking coffee is part of life in Manggar. The number of coffee shops that are located closely to each other around the center of Manggar makes it look very unique. This study aims to identify the visual characteristics of coffee shops signboard in Manggar in terms of typography, images, and colors. This research is done by using content analysis method which then interpreted by using semiotic approach. This research hopefully will show the characteristic of city of Manggar which represented by the characteristic of coffee shops signboard in Manggar.Keywords: Signboard, coffee shop, Manggar, East Belitung, semiotic. visual